2019
DOI: 10.1097/ico.0000000000002112
|View full text |Cite
|
Sign up to set email alerts
|

Cenegermin in Pediatric Neurotrophic Keratopathy

Abstract: Purpose: We report a case of neurotrophic keratopathy (NK) arising after surgery for rhabdomyosarcoma of the jaw successfully treated with Cenegermin eye drops (Oxervate; Dompé Farmaceutici, Milan, Italy) in a 3-year-old boy. Methods: At the age of 1 year, the boy underwent surgery for rhabdomyosarcoma of the jaw, followed by radiotherapy. Subsequent NK was initially treated with preservative-free artificial tears, topical combination of dexamethasone 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 4 publications
1
19
0
1
Order By: Relevance
“…[ 1 , 4 ] Among uncommon causes that can lead to NK, congenital diseases such as familial dysautonomia (Riley-Day syndrome), Goldenhar-Gorlin syndrome, Mobius syndrome, and familial trigeminal anesthesia have also been described. [ 2 , 5 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1 , 4 ] Among uncommon causes that can lead to NK, congenital diseases such as familial dysautonomia (Riley-Day syndrome), Goldenhar-Gorlin syndrome, Mobius syndrome, and familial trigeminal anesthesia have also been described. [ 2 , 5 ]…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, only few cases of patients with congenital NK treated with Cenegermin have been reported. [ 2 , 5 ]…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, various case reports showed the successful outcomes of this treatment in pediatric NK owing to different etiologies. 10 , 13 , 14 , 15 , 16 , 17 On the other hand, a recent case series (9 eyes of 8 pediatric patients) provided modest support for the efficacy of NGF in this setting, reporting an improvement of corneal ulcer stage in 5 eyes and best-corrected visual acuity in 2 eyes. 7 However, in our case it was not possible to use this drug and obtain its reimbursement due to local regulatory issues.…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies have shown that cenegermin is safe and effective for use in pediatric patients ≥ 2 years old and is now permitted for use in children in the USA [49]. The most common side effects of cenegermin include eye and eyelid pain, inflammation, increased tearing, and foreign body sensation in the eye [50]. No current concensus on timing of cenegermin for the treatment of NK is established; however, it is generally reserved for treatment of moderate to severe NK to aid corneal healing and prevent progression to corneal melt.…”
Section: Cenegermin (Oxervate™)mentioning
confidence: 99%
“…Nicergoline is a derivative of ergoline that is typically used to treat cognitive impairment due to degenerative dementia or stroke [50,51]. Administered orally, the drug is thought to increase the healing of corneal epithelial wounds by increasing levels of NGF in the cornea and lacrimal glands, as evidenced by rat studies [42,52].…”
Section: Nicergoline (Sermion®)mentioning
confidence: 99%